2022
DOI: 10.3390/ijerph19042324
|View full text |Cite
|
Sign up to set email alerts
|

The Gram-Negative Bacilli Isolated from Caves—Sphingomonas paucimobilis and Hafnia alvei and a Review of Their Involvement in Human Infections

Abstract: The opportunistic infections with Gram-negative bacilli are frequently reported. The clinical studies are focused on the course of human infectious and very often the source of infection remain unclear. We aim to see if the Gram-negative bacilli isolated from a non-contaminated environment—the caves—are reported in human infections. Eleven samples were collected from six Romanian caves. We used the standard procedure used in our clinical laboratory for bacterial identification and for antibiotic susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…A retrospective study by Ionescu et al showed that at least 43% of patients with bloodstream infections had a hospital-acquired infection and 37% had acquired one from the community. 12 Thus, this case of a 23-year male is quite peculiar because he is not only an immunocompetent person but also had no health care contact before this visit to our hospital.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective study by Ionescu et al showed that at least 43% of patients with bloodstream infections had a hospital-acquired infection and 37% had acquired one from the community. 12 Thus, this case of a 23-year male is quite peculiar because he is not only an immunocompetent person but also had no health care contact before this visit to our hospital.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of the studies showed resistance against penicillin and cephalosporin. 7 One study reported that more than 50% of S. paucimobilis strains were resistant to beta-lactams, followed by fluoroquinolone (25.6%) and sulfonamides (20.9%). 6 Trimethoprim-sulfamethoxazole, chloramphenicol, ciprofloxacin, and aminoglycosides have all been successfully used to treat this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacteria have been reported to be zoonotic pathogens and to cause infections in humans, with the exception of Oceanbacillus sp. and Ruegeria sp., suggesting a potential fish-to-human bacterial transmission ( Savini et al, 2009 ; Bandeira Junior et al, 2018 ; Terceti et al, 2019 ; Yin et al, 2019 ; Cao et al, 2021 ; Enosi Tuipulotu et al, 2021 ; Ribeiro et al, 2021 ; Al-Eqabi et al, 2022 ; Alzahrani et al, 2022 ; Choi and Choi, 2022 ; Ionescu et al, 2022 ). Among these known pathogens in marine fish, one unreported bacterial strain in the marine-cultured fish L. crocea was characterized and named K. kristinae_LC .…”
Section: Discussionmentioning
confidence: 99%